Combined Intrathoracic and Subcutaneous Splenosis Discovered 51 Years after Abdominal Trauma. (8th July 2015) - Gleason, James Benjamin; Hadeh, Anas; Diacovo, Maria Julia; Schroeder, Jonathan Ryan
Abstract : Splenosis is a rare condition that results from the autotransplantation of splenic parenchyma into unexpected locations such as the abdomen or subcutaneous tissue. In the presence of coexisting injury to the diaphragm intrathoracic transplantation can occur emerging as single or multiple pleural-based masses. This occurs after traumatic rupture of the spleen and is usually asymptomatic, only to be discovered incidentally on routine thoracic or abdominal imaging. To our knowledge this is the third documented case of combined intrathoracic and subcutaneous splenosis found in English literature. This occurred in a 71-year-old male involved in a motor vehicle accident at age 19 requiring urgent splenectomy. He has a significant cigarette smoking history and was referred to our hospital for further evaluation of an abnormality seen on shoulder X-ray.